Plan Schemes Memorandum for the Year 1995-96 Government of Haryana - Planning Commission (Planning Commission, 2001)
Scheme for the Multiplication and Distribution of improved Seeds and Development of Seeds Farms Rs.6,60,000. The object of the scheme is to produce genetically high quality seeds at the Government Seed Farms under direct supervision of the departmental staff for their distribution amongst the farmers.
Planning Department Government of Haryana